Assessing non-synthetic crosslinkers in biomaterial inks based on polymers of marine origin to increase the shape fidelity in 3D extrusion printing - Carvalho, Duarte Nuno (2023)
In the past decade, there has been significant progress in 3D printing research for tissue engineering (TE) using biomaterial inks made from natural and synthetic compounds. These constructs can aid in the regeneration process after tissue loss or injury, but achieving high shape fidelity is a challenge as it affects the constructâ s physical and biological performance with cells. In parallel with the growth of 3D bioprinting approaches, some marine-origin polymers have been studied due to their biocompatibility, biodegradability, low immunogenicity, and similarities to human extracellular matrix components, making them an excellent alternative to land mammal-origin polymers with reduced disease transmission risk and ethical concerns. In this research, collagen from shark skin, chitosan from squid pens, and fucoidan from brown algae were effectively blended for the manufacturing of an adequate biomaterial ink to achieve a printable, reproducible material with a high shape fidelity and reticulated using four different approachesÂ (phosphate-buffered saline, cell culture medium, 6% CaCl2, and 5 mM Genipin). Materials characterization was composed by filament collapse, fusion behavior, swelling behavior, and rheological and compressive tests, which demonstrated favorable shape fidelity resulting in a stable structure without deformations, and interesting shear recovery properties around the 80% mark. Additionally, live/dead assays were conducted in order to assess the cell viability of an immortalized human mesenchymal stem cell line, seeded directly on the 3D printed constructs, which showed over 90% viable cells. Overall, the Roswell Park Memorial Institute cell culture medium promoted the adequate crosslinking of this biopolymer blend to serve the TE approach, taking advantage of its capacity to hamper pH decrease coming from the acidic biomaterial ink. While the crosslinking occurs, the pH can be easily monitored by the presence of the indicator phenol red in the cell culture medium, which reduces costs and time.